STRATEGI KOMUNIKASI SANGGAR LATAH TUAH PEKANBARU DALAM MENARIK MINAT ANGGOTA PECINTA SENI - Adita Puji Ardiyanta; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Sanggar Latah Tuah is one of the art communities that has existed and survived long enough until this day, and one of the things that play a role in this is the communication and strategy that is carried out. Therefore, this study aims to find out the communication strategies carried out by Sanggar Latah Tuah in attracting members of art lovers, by identifying the formulation, implementation, and evaluation carried out on a predetermined strategy.The method used in this research is a qualitative method that is descriptive and data collection techniques through in-depth interviews, observation, and documentation studies. Data were obtained from interviews with four research informants, namely the general chairman, graphic design, and members of Sanggar Latah Tuah.Broadly speaking, the strategy is carried out through three stages: first, the formulation of strategies. This stage is a step that must be taken in planning communication. Second, strategy implementation. In this stage the process of implementing the strategy runs and the use of information systems and linking resources with the performance of the community or organization. And third, strategy evaluation. This stage is to measure the extent to which the strategy has been achieved. Based on the research results obtained show that the communication strategy carried out by Sanggar Latah Tuah is through a direct approach through the activities carried out by Sanggar Latah Tuah and through social media by disseminating information relating to each activity that will be carried out. From the results of this study, the researchers concluded that the communication strategy carried out by Sanggar Latah Tuah in attracting members of art lovers had been fully carried out and was quite effective, even though it had not been perfectly structured in accordance with the theory of communication strategies this could be seen from the increasing number of members. and the existence of Latah Tuah itself which is able to survive long enough in the arts.Keyword : strategy, communication, community, interest, art